NILAI-NILAI MORAL PADA SYAIR LAGU BERBAHASA JAWA KARYA SUJIWO TEJO - Febriansyah, Iqbal Fauzan; Nurchasanah, Nurchasanah (Jurnal Pembelajaran Sastra, 2023)
Songs can be used to express one's feelings or opinions about something. Sujiwo Tejo's songs, for example, excel in conveying deep and motivating moral principles through meaningful lyrics. Moral value debates are invariably linked to issues of human behavior, and issues of human behavior cannot be isolated from the term "character." The design of the Merdeka Curriculum curriculum, which is aimed at fulfilling the Pancasila Student Profile with character, is one method of implementing character education. Based on the description above, the purpose of this research is to describe the moral values in the lyrics of Javanese songs by Sujiwo Tejo from the album "Pada Suatu Ketika" and its relation to the profile of Pancasila pupils in the Merdeka Curriculum. This study takes a qualitative approach. Researchers discovered fifteen moral values in the album "Pada Suatu Ketika" that fell under the category of spiritual moral values and ten social moral values. Five of the six dimensions of the Pancasila student profile are relevant to the moral values discovered.